C+ ion implanted single crystal diamond with amorphous surface for efficient oxygen evolution catalysis. Issue 12 (15th June 2023) - Tu, Juping; Wang, Yong; He, Jian; Liu, Jinlong; Jia, Baorui; Chen, Liangxian; Wei, Junjun; Li, Chengming
Abstract: Oxygen evolution reaction (OER) is critical in water splitting for green hydrogen gas production due to its sluggish kinetics; however, commercial OER catalysts commonly suffer from high cost, low catalytic activity and poor stability. Herein, we developed a C + ion implantation method to modify single crystal diamond, and the resultant surface amorphous layer not only raised the active site number but also increased the content of the C=O group, thus significantly improving the OER activity. The C + ion implanted high-temperature and high-pressure (C + -HTHP) and chemical vapor deposition (C + -CVD) diamonds both exhibit low OER overpotential with η10 of 317 mV and 325 mV respectively, superior to those of HTHP diamond (360 mV), CVD diamond (395 mV) and RuO2 (364 mV). The potentiostatic testing shows that the C + implanted diamonds almost didn't undergo the rise of OER overpotential upon catalysis for more than 12 h at a current density of 10 mA cm −2, suggesting a high catalytic stability, owing to the strong bonding between single crystal diamond and amorphous carbon layer. For the first time, we utilized carbon ion implantation to prepare diamond-based high-performance OER catalyst, which broadens the understanding of carbon-based materials in OER catalysis.